3D MODELING & BIM Data Modeling & Management for AECO Industry A virtual meeting for real scenarios (diségno, 2020)
At the present time, connection, collaborative work and digital management tools are becoming increasingly important: in a sort of rush to digitization, in different and various fields, new technologies and strategies become mature. In the construction industry, as well as in the design word and in cultural heritage valorization, it is necessary to use digital and advanced tools and processing, which are based on digital modeling, in all its forms (read more).